Motivation and will - Vásquez, Stella Maris (2009)
The paper analyzes the relationship between motivation and volitional processes as described by current motivation theories. The root of the separation between both moments of behavioris traced back to Tetens and Kant’s threefold view of the mind. Sensory perception is reduced to feeling and the will to energy without a proper object. The history of this conception isoutlined. Nuttin’s motivation theory is presented as an alternative to the limitations of other contemporary theories. Some educational consequences are sketched out.